E-Learning dalam Pengajaran Kosakata Bahasa Arab di Madrasah Tsanawiyah - Mahyudin, Erta; Gusiar, Azizah Nurvia; Wahab, Muhbib Abdul; Albantani, Azkia Muharom; Maulana, Tengku (Kalimatuna: Journal of Arabic Research, 2022)
This study is motivated by the emergence of the Covid-19 Virus, which has resulted in numerous changes in education, one of which is the usage of learning media. This study intends to expose the e-learning process as a model for teaching Arabic vocabulary, as well as the students' control over the Arabic vocabulary after learning through e-learning. The researcher used a quantitative strategy as well as a descriptive technique in his investigation. The participants in this study are eighth-grade students. Observation, personal interview, test, and questionnaire were utilized to collect data in this study. This study shows how e-learning was used in this school employing simultaneous e-learning, and the students were enthusiastic about teaching vocabulary using the internet.